Understanding Factors Affecting Local Administration Reform on Accrual-Based Financial Statements - Sukamdaru, Haryono; subroto, Bambang; Mardiati, Endang (Universitas Negeri Malang, 2017)
This study is set out to analyze the understanding of local government officials on the accrual-based financial statements. The analyses are performed on the effects of training, education, working experience, and the quality of information technology to comprehending accrual-based financial statements. Furthermore, the data are collected using questionnaires, and distributed to all officials responsible for financial statements and financial administration officials in all working units (SKPD) in Probolinggo Municipality, and the used samples are 57 respondents. Data analysis method is double regression. The result of this study indicates that the training and working experience positively influences on the comprehension of accrual-based financial statements. The quality of education and information technology do not bring a pass to the understanding of accrual-based financial statements. Keywords : Accrual-based financial statements understanding, education, information technology quality, training, work experience